S.T.O.P Survival Skills - Zulkifli, Mohamad Firdaus; BINTI A.HAMID, RAHAYU (Applied Information Technology And Computer Science, 2022)
Survival skills are techniques that can be used to sustain life in any type of environment or natural disaster. The unawareness of the people on the importance of survival situational become the main factor of game development. The game content was developed as a mobile game application based on real-life survival skills and will be tested on the target user within the age range 15 years old and above. The agile model was chosen because of the flexibility control over the progress of the task during the game development. The game was developed using Unity and Photoshop and using C# as the programming language with Visual Studio software. This game expected able to bring the user through the real wild nature and emergency and guide them on what they should do to survive the wilderness. The user is indirectly able to gain information on basic survival skills while enjoying the game.